2014
DOI: 10.1007/s13595-014-0426-9
|View full text |Cite
|
Sign up to set email alerts
|

Estimates of genetic parameters for growth and wood properties in Eucalyptus pellita F. Muell. to support tree breeding in Vietnam

Abstract: & Key message Eucalyptus pellita demonstrated good growth and wood quality traits in this study, with young plantation grown timber being suitable for both solid and pulp wood products. All traits examined were under moderate levels of genetic control with little genotype by environment interaction when grown on two contrasting sites in Vietnam. & Context Eucalyptus pellita currently has a significant role in reforestation in the tropics. Research to support expanded of use of this species is needed: particula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
29
0
6

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(43 citation statements)
references
References 34 publications
(48 reference statements)
8
29
0
6
Order By: Relevance
“…The analysis of the heritability coefficients within families showed that they were much lower than the heritability based on a family average. Other studies have found similar results in clones of Eucalyptus L'Hér (Santos et al 2015) and Eucalyptus pellita F. Muell (Hung et al 2015), which agrees with this work, since both species are perennial. This result allows inferring that the selection based on the average of the families can be more efficient than within families.…”
Section: I2supporting
confidence: 92%
“…The analysis of the heritability coefficients within families showed that they were much lower than the heritability based on a family average. Other studies have found similar results in clones of Eucalyptus L'Hér (Santos et al 2015) and Eucalyptus pellita F. Muell (Hung et al 2015), which agrees with this work, since both species are perennial. This result allows inferring that the selection based on the average of the families can be more efficient than within families.…”
Section: I2supporting
confidence: 92%
“…Density, diameter at age 2 (growth), volumetric shrinkage, acoustic velocity and stiffness all have significantly large heritability, suggesting that breeding for these traits is achievable. The heritabilities are similar to those reported for other eucalypt species (Hung et al 2014;Hein et al 2012;Blackburn et al 2010;Blackburn et al 2014;Hamilton et al 2008). Wood processors pay premiums for stable and stiff timber, while forest growers often prefer to have fastgrowing trees as to shorten rotation lengths increasing profitability.…”
Section: Resultssupporting
confidence: 76%
“…Wood density is of particular importance because it can have strong impact on wood stiffness and strength [36]. The present study found that the genetic correlations between wood density and mechanical properties (MoE and MoR) were favourable.…”
Section: Genetic Correlation Among Wood Propertiesmentioning
confidence: 45%
“…The genetic correlation between density and stiffness was favourable in the present study, suggesting that the genetic correlation between MFA and stiffness is also likely to be favourable. Thus, wood with high stiffness has high density and small MFA [36]. However, further research may be required to confirm the correlation between MFA and stiffness.…”
Section: Genetic Correlation Among Wood Propertiesmentioning
confidence: 99%